2016
DOI: 10.3904/kjim.2015.392
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of pathologic examination of non-neoplastic kidney in patients with upper urinary tract malignancies

Abstract: Background/Aims:While surgical resection remains the standard of care in the treatment of upper urinary tract malignancies, nephrectomy is a risk factor for the development of chronic kidney disease (CKD). The aim of this study was to determine whether histologic evaluation of non-neoplastic kidney could enable early identification of unrecognized kidney disease and could be of prognostic value in predicting postoperative renal outcomes.Methods:We retrospectively analyzed 51 patients with upper urinary tract m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Additional glomerular, tubulo-interstitial or vascular nonneoplastic diseases were observed distant from the putative tumor bed in 18.9% of our cases. This incidence is in line with most published data (15-29.4%), which depend, though, on their specific pathologic definition [6][7][8]11]. This frequency may seem high in comparison to the general population, but a substantial part of the lesions we described here are related to diabetes mellitus, hypertension, or TIN cases, disorders that are recognized risk factors for RCC.…”
Section: Discussionsupporting
confidence: 92%
“…Additional glomerular, tubulo-interstitial or vascular nonneoplastic diseases were observed distant from the putative tumor bed in 18.9% of our cases. This incidence is in line with most published data (15-29.4%), which depend, though, on their specific pathologic definition [6][7][8]11]. This frequency may seem high in comparison to the general population, but a substantial part of the lesions we described here are related to diabetes mellitus, hypertension, or TIN cases, disorders that are recognized risk factors for RCC.…”
Section: Discussionsupporting
confidence: 92%
“…NNRD can be found in 9 to 38% of kidney and ureteral cancer patients (table 4) 6,9,12,[14][15][16][17][18][19][20][21][22] . Up to 90% of these diagnoses were not found at the initial pathologic evaluation, because pathologists focused on the renal neoplasm, and none of the patients in our cohort were initially diagnosed.…”
Section: Wementioning
confidence: 99%
“…It is shown that 5 to 25% of RCC patients have varying pathologies of chronic kidney disease and those with normal renal function are more likely to develop chronic kidney disease after nephrectomy. Such changes may cause impairment of renal function and reduce the patient’s quality of life [ 2 5 ]. Through examination of non-neoplastic renal parenchymal changes in 110 cancer-related nephrectomy specimens, Bijol et al showed that only 10% of the cases have unremarkable parenchyma and those with considerable pathological changes such as severe parenchymal scarring and more than 20% glomerulosclerosis had progressive worsening of renal function in 6-month follow-up after radical nephrectomy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%